2021
DOI: 10.1016/j.crmeth.2021.100011
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and accurate agglutination-based testing for SARS-CoV-2 antibodies

Abstract: We have developed a rapid, accurate, and cost-effective serologic test for SARS-CoV-2 virus, which caused the COVID-19 pandemic, on the basis of antibody-dependent agglutination of antigen-coated latex particles. When validated using plasma samples that are positive or negative for SARS-CoV-2, the agglutination assay detected antibodies against the receptor-binding domain of the spike (S-RBD) or the nucleocapsid protein of SARS-CoV-2 with 100% specificity and ∼98% sensitivity. Furthermore, we found that the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Importantly, none of the healthy serum samples generated scores >0 for either PS-spike or PS-control microbeads (Figure D), whereas all of the COVID-19 positive samples registered scores of >1 for PS-spike beads, and generally 0 for PS-control microbeads. When titrating positive serum with healthy serum, we found that CAT scores remained positive down to ∼1:10 dilutions (Figure S7), consistent with recent studies reporting traditional well-plate format agglutination assays for SARS-CoV-2 antibodies. , However, given that every sample or analytical standard would have a unique antibody composition (i.e., unique IgG:IgM:IgA:IgD:IgE ratio and total Ig/mL, both of which vary over time as the immune response evolves), it is not feasible or relevant to definitively report assay detection or quantitation limits, consistent with other reports. , For several samples, the PS-control beads registered a score of 1, and these samples each required multiple rounds of centrifugation to clarify precipitate materials prior to testing. Similarly, we also tested some additional negative samples prepared as plasma which showed nonspecific positive signals on both PS-Spike and PS-Control microbeads (Figure S8); for this reason, the current assay format is only appropriate for testing with fasting serum samples, similar for a range of standard blood tests .…”
Section: Resultssupporting
confidence: 82%
“…Importantly, none of the healthy serum samples generated scores >0 for either PS-spike or PS-control microbeads (Figure D), whereas all of the COVID-19 positive samples registered scores of >1 for PS-spike beads, and generally 0 for PS-control microbeads. When titrating positive serum with healthy serum, we found that CAT scores remained positive down to ∼1:10 dilutions (Figure S7), consistent with recent studies reporting traditional well-plate format agglutination assays for SARS-CoV-2 antibodies. , However, given that every sample or analytical standard would have a unique antibody composition (i.e., unique IgG:IgM:IgA:IgD:IgE ratio and total Ig/mL, both of which vary over time as the immune response evolves), it is not feasible or relevant to definitively report assay detection or quantitation limits, consistent with other reports. , For several samples, the PS-control beads registered a score of 1, and these samples each required multiple rounds of centrifugation to clarify precipitate materials prior to testing. Similarly, we also tested some additional negative samples prepared as plasma which showed nonspecific positive signals on both PS-Spike and PS-Control microbeads (Figure S8); for this reason, the current assay format is only appropriate for testing with fasting serum samples, similar for a range of standard blood tests .…”
Section: Resultssupporting
confidence: 82%
“…First, we aimed to establish a PA test as a virus titration method using hACE2- bound latex beads (hACE2-beads) as a surrogate for the blood cells used in the HA test of influenza viruses. The hACE2-beads were prepared based on the method used for SARS-CoV-2 antigen-coated latex beads 10 (see the Online Methods). A suspension of the prepared beads showed a clear sedimentation pattern after overnight settling at a final concentration of 0.03% (Fig.…”
Section: Establishment Of a Particle Agglutination (Pa) Testmentioning
confidence: 99%
“…Immunoassays are widely used in biology and medicine for identifying antibodies in samples with common assays, including latex agglutination tests, lateral flow assays, and Luminex bead-based assays. Latex agglutination tests, for example, have been used to reveal the presence of antibodies within samples by the clumping or aggregation of antigen-coated latex beads, and depending on the format of the assay, have been used for determining immunity to viruses including SARS-CoV-2 [27][28][29][30], as well as detection of infection by bacteria or parasites [31,32]. Applying this principle, we reveal a strategy for the generation of epitope displaying polydiacetylene vesicles capable of being used in the visual detection of the presence of specific antibodies by target-specific binding to induce aggregation.…”
Section: Introductionmentioning
confidence: 99%